PENINGKATAN PENGETAHUAN MASYARAKAT MELALUI SOSIALISASI PENANGANAN PASCAPANEN REMPAH DI DESA WULUHAN KABUPATEN JEMBER - Dian Purbasari; Ning Puji Lestari; Sutarsi; Iwan Taruna (Jurnal Abdi Insani, 2023)
Spice plants are increasingly promising profits because demand for spice commodities occasionally increases. The potential for abundant spice plants in Kesilir Village does not align with its less-than-optimal development. The sale of spices in Kesilir Village is carried out in fresh form directly to intermediaries without post-harvest handling, so the selling price is low, namely IDR 5,000/kg. Post-harvest handling is essential to produce safe and quality processed products, increasing their selling value. This service program aims to increase community knowledge regarding post-harvest handling practices for spice plants to improve the quality and quality of the harvest. The methods used are lectures, discussions (focus group discussions), and evaluation (pre-test and post-test). The partners for this service activity are residents of Kesilir village consisting of young women, housewives, mothers of PKK members, and community leaders. The results of the activity showed that there was an increase in partners' knowledge after being given material related to post-harvest handling of spices. More than 80% of activity participants understood the objectives and good post-harvest handling techniques to be applied to spices. Furthermore, assistance and training are needed to develop processed spice products in Kesilir village as a follow-up activity.